Integrated Surgical and Anesthetic Management of Pediatric Small Bowel Obstruction Due to Foreign Body Ingestion: A Comparative Case Series on Anatomical and Perioperative Implications (Razi Medical Journal, 2025)
We conducted a retrospective review of three young female pediatric patients (aged 2, 3, and 4 years) who presented to our institution between May 2020 and March 2022 with SBO secondary to FB ingestion, all of whom were managed via laparotomy and enterotomy. This case series provides a comparative analysis of the clinical presentation, diagnostic trajectory, surgical findings, and, most importantly, perioperative anesthetic management in one patient with a history of neonatal jejunal atresia repair and two patients with anatomically normal GI tracts. All three patients successfully underwent surgical removal of the FB and experienced uncomplicated postoperative courses (Length of Stay: 4‒7 days). In the two anatomically normal patients (aged 3 and 4), impaction occurred predictably at the ileocecal valve (ICV)-(Photograph 4). Conversely, the post-surgical patient (aged 2) demonstrated a more proximal obstruction in the dilated jejunum, immediately adjacent to the previous anastomosis. Significantly, the anesthetic management across all cases was characterized by aggressive fluid resuscitation, meticulous correction of electrolyte imbalances, and stringent aspiration prophylaxis via Rapid Sequence Induction (RSI). This protocol directly addressed the inherent high-risk profile of this patient cohort and was instrumental in achieving the favorable clinical outcomes. The location of foreign body-induced SBO in children is fundamentally dictated by the underlying GI anatomy, which mandates a precisely tailored surgical strategy. However, optimal patient outcomes are inextricably linked to an integrated, multidisciplinary approach. Specialized pediatric anesthetic protocols, which prioritize aspiration prevention, meticulous fluid and electrolyte homeostasis, and effective pain management, are foundational elements for minimizing morbidity and accelerating patient recovery.
Keywords: Small Bowel Obstruction, Foreign Bodies, Pediatrics, Ileocecal Valve, Intestinal Atresia